2002
DOI: 10.1007/s00421-002-0711-4
|View full text |Cite
|
Sign up to set email alerts
|

Toward the optimal waveform for electrical stimulation of human muscle

Abstract: Electrical stimulation of the quadriceps muscle was used to elicit 4-min isometric contractions at 10% of the maximal voluntary contraction (MVC) in four male and three female subjects. The effect of four waveforms, including Russian, interferential, sine, and square, on the mean stimulation current required to achieve the desired contraction force, subjective comfort, and physiological responses was studied. Interferential stimulation, even at full power, could not elicit a sustained contraction at 10% MVC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 23 publications
(21 reference statements)
1
65
0
Order By: Relevance
“…Several studies showed interesting data in other applications on the influence of the waveform on the efficacy and the response of nerve stimulation. [16][17][18][19]21 Besides, more and more studies have revealed that some waveforms, like biphasic waveforms, are preferred by the patients 14,15 for ES.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies showed interesting data in other applications on the influence of the waveform on the efficacy and the response of nerve stimulation. [16][17][18][19]21 Besides, more and more studies have revealed that some waveforms, like biphasic waveforms, are preferred by the patients 14,15 for ES.…”
Section: Discussionmentioning
confidence: 97%
“…7,13 On the other hand, these results also suggest that it is possible to have similar results using waveforms with different charge per time and power. This can be important for patient's comfort 16,22 or for energy consumption of stimulator implants. Comparison of electrical charges per second and of average power is justified, because it is critical for producing changes in biological systems when using ES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase of pain and discomfort level depends on current intensity during electrical stimulation. It has been reported that some subjects complained severe pain with electrical stimulation for muscle strengthening [29]. This pain could be so uncomfortable that many subjects prefer not using this modality even though there was good therapeutic [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some subjects complained severe pain with electrical stimulation for muscle strengthening [29]. This pain could be so uncomfortable that many subjects prefer not using this modality even though there was good therapeutic [29]. Thus, current intensity which was set for ES must be considered a balance between tolerance pain and maximum muscle loading.…”
Section: Discussionmentioning
confidence: 99%